Hematologic safety of palbociclib in combination with endocrine therapy in patients with benign ethnic neutropenia and advanced breast cancer. Issue 19 (22nd June 2021) - Lynce, Filipa; Blackburn, Matthew J.; Zhuo, Rebecca; Gallagher, Christopher; Hahn, Olwen M.; Abu‐Khalaf, Maysa; Mohebtash, Mahsa; Wu, Tianmin; Pohlmann, Paula R.; Dilawari, Asma; Tiwari, Shruti R.; Chitalia, Ami; et al.
Abstract : Background: Cyclin‐dependent kinase 4/6 (CDK4/6) inhibitors, including palbociclib, are approved to treat hormone receptor (HR)‐positive/human epidermal growth factor receptor 2 (HER2)‐negative advanced breast cancer (ABC) and are associated with hematologic toxicity. African American women, who are underrepresented in CDK4/6 inhibitor clinical trials, may experience worse neutropenia because of benign ethnic neutropenia. The authors specifically investigated the hematologic safety of palbociclib in African American women with HR‐positive/HER2‐negative ABC. Methods: PALINA was a single‐arm, open‐label, investigator‐initiated study of palbociclib (125 mg daily; 21 days on and 7 days off) plus endocrine therapy (ET) in African American women who had HR‐positive/HER2‐negative ABC and a baseline absolute neutrophil count ≥1000/mm 3 (ClinicalTrials.gov identifier NCT02692755). The primary outcome was the proportion of patients who completed 12 months of therapy without experiencing febrile neutropenia or treatment discontinuation because of neutropenia. Single nucleotide polymorphism analysis was used to assess Duffy polymorphism status. Results: Thirty‐five patients received ≥1 dose of palbociclib plus ET; 19 had a Duffy null polymorphism (cytosine/cytosine). There were no reports of febrile neutropenia or permanent study discontinuation because of neutropenia. Significantly more patients with the Duffy null versus the wild‐type variant had grade 3 and 4 neutropenia (72.2% vs 23.1%; P = .029) and required a palbociclib dose reduction (55.6% vs 7.7%; P = .008). Patients with the Duffy null versus the wild‐type variant had lower overall relative dose intensity (mean ± SD, 81.89% ± 15.87 and 95.67% ± 5.89, respectively; P = .0026) and a lower clinical benefit rate (66.7% and 84.6%, respectively). Conclusions: These findings suggest that palbociclib is well tolerated in African American women with HR‐positive/HER2‐negative ABC. Duffy null status may affect the incidence of grade 3 neutropenia, dose intensity, and possibly clinical benefit. Abstract : Palbociclib is well tolerated in patients with hormone receptor–positive/HER2–negative advanced breast cancer and benign ethnic neutropenia. Duffy null status appears to affect the incidence of grade 3 neutropenia, dose intensity, and possibly clinical response.